2023
DOI: 10.3390/curroncol30030258
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Mean Platelet Volume (MPV) with Cancer: A Systematic Review with a Focus on Disease Outcome on Twelve Types of Cancer

Abstract: Inflammatory proteins activate platelets, which have been observed to be directly related to cancer progression and development. The aim of this systematic review is to investigate the possible association between Mean Platelet Volume (MPV) and cancer (diagnostic capacity of MPV, relation to survival, the severity of the disease, and metastasis). A literature review was performed in the online database PubMed and Google Scholar for the period of 2010–2022. In total, 83 studies including 21,034 participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 129 publications
0
6
1
Order By: Relevance
“…To our knowledge, however, there are no previous prospective studies to be able to compare the prospective associations of MPV and PDW with lung cancer risk described in our study. Several case–control studies have previously reported higher MPV at lung cancer diagnosis [ 14 ], in contrast to our findings, but a case–control study examining patients with advanced lung cancer has reported lower MPV at diagnosis, in addition to higher platelet count [ 31 ]. Although prospective associations may be retained to cancer diagnosis, studies recruiting cases and controls at cancer diagnosis would also reflect cancer-related changes and could thus be influenced by reverse causality, hence potentially explaining the differences between previous studies and our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, however, there are no previous prospective studies to be able to compare the prospective associations of MPV and PDW with lung cancer risk described in our study. Several case–control studies have previously reported higher MPV at lung cancer diagnosis [ 14 ], in contrast to our findings, but a case–control study examining patients with advanced lung cancer has reported lower MPV at diagnosis, in addition to higher platelet count [ 31 ]. Although prospective associations may be retained to cancer diagnosis, studies recruiting cases and controls at cancer diagnosis would also reflect cancer-related changes and could thus be influenced by reverse causality, hence potentially explaining the differences between previous studies and our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Little is known, however, about associations of platelet size with lung cancer risk. The available studies are few, with small number of patients, focused on lung cancer diagnosis and prognosis, and reporting mainly higher MPV and PDW in lung cancer patients compared to healthy controls [ 14 , 15 ]. To our knowledge, there are no studies evaluating prospectively associations of MPV or PDW with lung cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Activated platelets play a mediating role in tumor growth, invasion, abnormal angiogenesis, and metastasis [4,5]. It has been proved that platelet elevation is associated with adverse outcomes of many different cancers, including gastric cancer, pancreatic cancer, ovarian cancer, and endometrial cancer [6][7][8][9]. Meanwhile, lymphocytes are the key cell component of immune response and participate in the anti-tumor immune process.…”
Section: Introductionmentioning
confidence: 99%
“…A high MPV is associated with increased platelet production while a low MPV indicates decreased platelet production [ 22 ]. The biomarker role of MPV has been emphasized in different medical conditions including diabetes [ 23 ], metabolic syndrome [ 24 ], cancer [ 25 ], inflammatory bowel disease [ 26 ], preeclampsia [ 27 ], and ITP [ 16 ]. In ITP, an increased number of new platelets are formed in the bone marrow in response to excessive platelet destruction in the spleen.…”
Section: Introductionmentioning
confidence: 99%